Craniofacial Microsomia and Treacher Collins Syndrome Comprehensive Treatment of Associated Facial Deformities - Yates, David M.; Markiewicz, Michael R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The book provides a framework for diagnosis and treatment of the complex facial deformities found in craniofacial microsomia and Treacher Collins syndrome. These conditions are difficult to treat due to their complexity and variable presentation. The deformities may be mild or severe and merely cosmetic to life-threatening in nature. These conditions often manifest as complex facial deformities that require multiple surgical interventions. Timing is critical when treating these patients and knowing and choosing the correct operation is key to successful outcomes. This work provides a comprehensive approach in treating these complex patient populations, seeking to answer the following questions: When to operate versus when to wait? If operating is required what operation should be performed? What is the best orthodontic approach to the associated dental deformities that develop with these conditions? How should sleep apnea be evaluated and treated in this population? What is the best management for feeding patients with these conditions? Written by experts in the field, Craniofacial Microsomia and Treacher Collins Syndrome: Comprehensive Treatment of Associated Facial Deformities aims to provide the reader with literature based best practices in treating these children from the NICU through childhood and into adulthood.
Etiology and Anatomical Variance in Craniofacial Microsomia -- Initial Evaluation of a Patient with Craniofacial Microsomia -- A look at Breathing, Feeding/Swallowing, and Speech Impairment in Patients with Craniofacial Microsomia -- Extracraniofacial Manifestations of Craniofacial Microsomia -- Management of the Mandibular Deformity in the Growing Patient With Craniofacial Microsomia -- Surgical Management of Hemifacial Microsomia With Temporomandibular Joint Malformation -- Definitive Reconstruction of Associated Maxillomandibular Deformities in Craniofacial Microsomia -- Orthodontic Considerations in the Craniofacial Microsomia Patients -- Management of Hearing Loss in Patients with Treacher-Collins Syndrome and Hemifacial Microsomia -- Microtia Reconstruction in Patients with Craniofacial Microsomnia -- Correction of the Soft Tissue Deformities Associated with Craniofacial Microsomia: Facial Reanimation and Soft Tissue Grafting Techniques -- An Overview of Treatment and Recommendations for the Craniofacial Microsomia Patient -- Etiology and Anatomical Variation in Treacher Collins Syndrome -- Initial Evaluation of a Patient with Treacher Collins Syndrome -- A look at Breathing, Feeding, and Speech Problems in Patients with Treacher Collins Syndrome -- Associated Systemic Health Conditions Associated with Treacher Collins Syndrome -- Ophthalmologic Findings and Reconstruction of Soft Tissue Orbital Deformities: Coloboma and Lid Deformities -- Correction of Orbital Zygomatic Deformities in the Treacher Collins Patient -- Management of the Mandibular Deformity in Growing Patients with Treacher Collins Syndrome -- TMJ Total Joint Prosthesis in Treacher Col-lins Syndrome and Hemifacial Microsomia -- Definitive Correction of Associated Maxillomandibular Deformities in Treacher Collins Syndrome -- Principles of Orthodontic Management of Treacher Collins Syndrome -- Hearing loss and aural rehabilitation in patients with Treacher Collins Syndrome -- Reconstruction of the Ear Deformities Associated with Treacher Collins Syndrome -- Rhinoplasty in Patients with Treacher Collins Syndrome -- An Overview of Treatment Recommendations for the Treacher Collins Syndrome Patient.
Keywords: Surgery; Otorhinolaryngology; Surgery; Surgery; Otorhinolaryngology; Craniofacial Dysostosis